USE OF PROGESTERONE-BASED FTAI PROTOCOL FOLLOWED BY GnRH OR hCG TREATMENT ON DAY 6 POST-AI IN REPEAT BREEDER CATTLE - KUNDE, A A S; RAJU, M S; MURUGAVEL, K (The Indian Journal of Animal Reproduction, 2022)
Repeat breeder cattle (n=45) were synchronized using intravaginal progestational device (TRIU-B) basedCo-Synch protocol. On day 6 post artificial insemination (AI), all the animals were administered (i.m.) either 10μg GnRH analogue, (n=15), 1500 IU hCG (n=15) or normal saline (n=15). Pregnancy diagnosis was carriedout on day 45 post-AI. Jugular vein blood was collected on day 6 and day 12 post-AI for serum progesteroneestimations. On day 12 post-AI, serum progesterone values both overall as well as in the conceived animals werehigh (p
Keywords: Co-synch; Conception rate; GnRH; hCG; Progesterone